Manufacturing Process Improvement by Barcode Reader using Image Processing - Sutikamon Sukasem; Noppadol Maneerat; Jakkrit Thudthong; Chanathip Wongsomboon; Kuniaki Yajima; Kasemsuk Sepsirisuk (My University, 2024)
Manufacturing industries get perspective on the efficiency of their production process. This study focuses on improving the cycle time of the work process at the station related to barcode reading. This operation should be of minimal duration to result in shorter cycle times and resulting in increased production volumes while still maintaining quality and reducing production costs. Image processing methodology is applied to reading barcodes instead of using a barcode reader which creates clear image quality along with developing an application using Android Bridge (ABD) and ZXing libraries that can read 1D barcodes in many formats. More essentially, application development by multithreading programming can process barcode reading simultaneously at a time that meets the target cycle time. The result of this study proves that the process of reading barcodes by human work has taken 60 times per job cycle and the reading time was about 29 seconds, becoming reduced to 19.85 seconds, manpower can be reduced by 1 person and production cost as well. Moreover, this implementation eliminates human errors that are likely to occur from scanning barcodes in the wrong position. Therefore, this study has benefited the manufacturing industry achieve significantly increased productivity and efficiency.
Keywords: QR Code Applications and Technologies; Industrial Vision Systems and Defect Detection; Additive Manufacturing and 3D Printing Technologies